ImaginYouth—A Therapist-Guided Internet-Based Cognitive-Behavioral Program for Adolescents and Young Adults With Body Dysmorphic Disorder: Study Protocol for a Two-Arm Randomized Controlled Trial - Hartmann, Andrea S.; Schmidt, Michaela; Staufenbiel, Thomas; Ebert, David D.; Martin, Alexandra; Schoenenberg, Katrin (Frontiers in Psychiatry, 2021)
Background: Body dysmorphic disorder (BDD) is a relatively common mental disorder in adolescents and is characterized by severe negative psychosocial consequences and high comorbidity as well as high mortality rates, mainly due to suicides. While patients in Germany have health insurance-financed access to evidence-based outpatient treatments, i.e., cognitive-behavioral treatment (CBT), waiting lists are long. Furthermore, patients with BDD report diverse treatment barriers, primarily feelings of shame and the belief that they would be better off with treatments that would alter the perceived flaw(s). Given adolescents’ high affinity to electronic media, the accessibility of evidence-based care for this severe mental disorder could be improved by providing an internet-based therapist-guided CBT intervention. Methods: In a two-arm randomized controlled trial (N = 40), adolescents (15-21 years) with a primary diagnosis of BDD based on a semi-structured clinical expert interview will be randomly allocated to an internet-based therapist-guided CBT intervention or a supportive internet-based therapy intervention. Assessments will take place at baseline, after mid-intervention (after 6 weeks), post-intervention, and at 4-week follow-up. The primary outcome is expert-rated BDD symptom severity at the primary endpoint post-intervention. Secondary outcomes include responder and remission rates based on expert rating, self-reported BDD symptoms, and psychosocial variables associated with BDD. Interventions: The CBT-based intervention consists of six modules each comprising one to three sessions, which focus on psychoeducation, cognitive restructuring, work on self-esteem, exposure and ritual prevention, mirror retraining, and relapse prevention. A study therapist provides feedback after each session. The supportive therapy intervention consists of access to psychoeducational materials for the same 12-week period and at least one weekly supportive interaction with the study therapist. Conclusions: This is the first study to examine the feasibility and efficacy of an internet-based therapist-guided CBT intervention in adolescents with BDD. It could be an important first step to increase accessibility of care in this age group and for this severe and debilitating mental disorder. Registration: The study has been registered in the German Register of Clinical Studies (Deutsches Register Klinischer Studien; DRKS00022055).